Toothiana : queen of the Tooth Fairy armies / 3. - Joyce, William, 1957- (Joyce, William, 1957- Guardians, 2012)
Toothiana, Queen of the Tooth Fairies, who might be small, but is very powerful, faces off against Pitch, the Nightmare King.